"A More Careful Tender Nurse Cannot Be than My Dear Husband": Reassessing the Role of Men in Pregnancy and Childbirth in Ulster, 1780–1838. (January 2017) - Calvert, Leanne
Childbirth is generally viewed as a female activity, which had little participation from men. Drawing largely on the papers of the Crawford family, this article offers an alternative to the traditional picture of childbirth. It argues that men (as husbands, brothers, and fathers) were not only interested in pregnancy and childbirth, but that they also played an active role in these events. It also explores the roles played by men in domestic medicine and argues that the gendered boundaries of the family were not as fixed as they appear.